2018
DOI: 10.1007/s12298-018-0529-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Hevea brasiliensis in response to exogenous methyl jasmonate provides novel insights into regulation of jasmonate-elicited rubber biosynthesis

Abstract: The phytohomorne methyl jasmonate (MeJA) is known to trigger extensive reprogramming of gene expression leading to transcriptional activation of many secondary metabolic pathways. However, natural rubber is a commercially important secondary metabolite and little is known about the genetic and genomic basis of jasmonate-elicited rubber biosynthesis in rubber tree (). RNA sequencing (RNA-seq) of bark treated with 1 g lanolin paste containing 0.02% w/w MeJA for 24 h (M2) and 0.04% w/w MeJA for 24 h (M4) was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 83 publications
1
14
0
1
Order By: Relevance
“…wenyujin (Figs 3 and 4 ). One major regulatory mechanism of MeJA-mediated secondary metabolite production in many plants, is to control related genes in biosynthesis pathway [ 43 , 44 ]. Consistent with this regulatory mechanism, related genes in JA biosynthesis, JA signaling transduction, and terpenes biosynthesis pathway in C .…”
Section: Discussionmentioning
confidence: 99%
“…wenyujin (Figs 3 and 4 ). One major regulatory mechanism of MeJA-mediated secondary metabolite production in many plants, is to control related genes in biosynthesis pathway [ 43 , 44 ]. Consistent with this regulatory mechanism, related genes in JA biosynthesis, JA signaling transduction, and terpenes biosynthesis pathway in C .…”
Section: Discussionmentioning
confidence: 99%
“…In rubber trees (Hevea brasiliensis), natural rubber synthesis is the main metabolic activity in laticifers which are highly specialized cells that directly influence the yield of rubber [ 19]. Most studies in molecular biology, especially those using gene expression profiling, have paid close attention to rubber biosynthesis in laticifers [20][21][22][23][24][25]. Previously, we have evaluated the expression stability of 22 reference genes across abundant laticifer samples, including latex regenerations, hormone treatments, tappings, individual trees and genotypes of Hevea [ 26,27].…”
mentioning
confidence: 99%
“…Previous studies demonstrated that the application of MeJA induced the accumulation of different secondary metabolites in several plant species, including Lycoris chinensis ( Mu et al, 2009 ), Dendrobium officinale ( Jiao et al, 2018 ), Physalis angulata L. ( Zhan et al, 2020 ), Isatis tinctoria L. ( Gai et al, 2019 ), and Vitis labrusca L. ( Moro et al, 2020 ). One major regulatory mechanism of MeJA-mediated secondary metabolite production in many plants is through the control of pathway related genes ( Liu et al, 2018 ; Li et al, 2019a ; Li W. et al, 2020 ). For example, the expression of some genes in terpenoid indole alkaloid (TIAs) pathways was induced by MeJA treatment in Catharanthus roseus ( Pan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methyl jasmonate treatment not only induces the expression of genes involved in JA biosynthetic pathways, but it also can induce JA signaling pathways ( Liu et al, 2018 ; Li W. et al, 2020 ). Similar results were observed in the present study, wherein RNA-seq and metabolite profiling suggested that the expression of putative JA biosynthesis genes ( AOC and OPR ) and JA signaling pathway genes ( JAR and MYC ) were upregulated.…”
Section: Discussionmentioning
confidence: 99%